CO2 mineralization in the production of sustainable concrete - De la Varga, Igor; Sargam, Yogiraj; Alexio, Daniel Martins (Revista Ingeniería de Construcción, 2024)
As the concrete industry continues to grapple with the challenge of reducing its carbon footprint, CO2 mineralization technologies offer a practical and scalable solution. These technologies enable the integration of CO2 as a valuable raw material, transforming waste emissions into durable mineral compounds during the concrete production process. This study investigates the implementation of CO2 mineralization in fresh concrete, analyzing its effects on key material properties such as strength and durability. Experimental results reveal that the process not only ensures equivalent compressive strength of concrete with a reduced cement content, but also contributes to reductions in embodied carbon compared to traditional methods. Furthermore, the study underscores the role of this approach in supporting the industry’s decarbonization efforts, aligning with global sustainability goals. The findings highlight CO2 mineralization as a pivotal step toward the creation of more sustainable construction materials, offering both environmental and economic benefits. These conclusions demonstrate the transformative potential of this technology in advancing the sustainability of concrete production while addressing the pressing demand for eco-friendly construction practices.